Human Neonatal Thymus Mesenchymal Stem Cells Promote Neovascularization and Cardiac Regeneration - Shuyun Wang; Shan Huang; Lianghui Gong; Zhize Yuan; Joshua Wong; Jeffrey Lee; Ming-Sing Si (Stem Cells International)
Newborns with critical congenital heart disease are at significant risk of developing heart failure later in life. Because treatment options for end-stage heart disease in children are limited, regenerative therapies for these patients would be of significant benefit. During neonatal cardiac surgery, a portion of the thymus is removed and discarded. This discarded thymus tissue is a good source of MSCs that we have previously shown to be proangiogenic and to promote cardiac function in an in vitro model of heart tissue. The purpose of this study was to further evaluate the cardiac regenerative and protective properties of neonatal thymus (nt) MSCs. We found that ntMSCs expressed and secreted the proangiogenic and cardiac regenerative morphogen sonic hedgehog (Shh) in vitro more than patient-matched bone-derived MSCs. We also found that organoid culture of ntMSCs stimulated Shh expression. We then determined that ntMSCs were cytoprotective of neonatal rat cardiomyocytes exposed to H2O2. Finally, in a rat left coronary ligation model, we found that scaffoldless cell sheet made of ntMSCs applied to the LV epicardium immediately after left coronary ligation improved LV function, increased vascular density, decreased scar size, and decreased cardiomyocyte death four weeks after infarction. We conclude that ntMSCs have cardiac regenerative properties and warrant further consideration as a cell therapy for congenital heart disease patients with heart failure.